Phylogenetic of Sumatran Clarias batrachus based COI Gene - Cinthya Fitri Hardianti; Djong Hon Tjong; Mansyurdin; Syaifullah; Dewi Imelda Roesma (Malaysian Journal of Science and Advanced Technology, 2022)
Clarias batrachus is a species of fish that can be found in Sundaland. The separation of Sundaland resulted in the separation of the islands, one of which was the island of Sumatra. The island of Sumatra is divided into west and east sides by the Bukit Barisan mountains. So, it is necessary to study the phylogenetic of C. batrachus. The CO1 gene is one of the mtDNA genes that can be used for phylogenetic studies. This study was conducted to determine the geographical relationship to the phylogenetic relationship of C. batrachus populations in Sumatra and other populations in Southeast Asia using the CO1 gene and the relationship between geographic isolation in the eastern and western watersheds of Sumatra. Based on 504 bp of C. batrachus CO1 gene sequence and 19 comparison sequences, three sub-clusters with two subspecies were formed.